Bibliometric Analysis of Blended learning Mathematics in Scientific Publications Indexed by Scopus - Ika Eryanti; Joko Soebagyo (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2021)
Research of blended learning in mathematics using the bibliometric method is still relatively rare. Therefore the novelty of this research is through the method used bibliometric analysis, data sources from Scopus database with restrictions on articles published in 2011 until 2021 analyzed with Publish or Perished (PoP ) application and visualization using Vosviewer. The sample of this research is scientific articles about blended learning mathematics indexed by Scopus published in the last ten years, from 2011 to 2021, as many as 136 scientific articles. The research method used is a bibliometric analysis conducted on 136 publications on blended learning mathematics learning on the Scopus database. Data analysis carried out is citation analysis, publication trend analysis, trend analysis, and analysis of author keywords. Research articles on blended learning mathematics learning published in Scopus indexed journals have generally experienced positive growth from year to year. The most citations to articles related to blended learning occurred in 2019 with 107 article citations., the articles that were used the most as references in these writings had a good impact on the creation of knowledge related to blended learning mathematics and research opportunities. Keywords that are rarely used related to blended learning in mathematics learning are analysis and Schoology. These two keywords can be a reference for further research in the future. It indicates that the opportunity to research this topic is still extensive.